Religion and Innovation - Roland Benabou; Davide Ticchi; Andrea Vindigni (Institute for the Study of Labor (IZA), 2015)
In earlier work (Bénabou, Ticchi and Vindigni 2013) we uncovered a robust negative association between religiosity and patents per capita, holding across countries as well as US states, with and without controls. In this paper we turn to the individual level, examining the relationship between religiosity and a broad set of pro- or anti-innovation attitudes in all five waves of the World Values Survey (1980 to 2005). We thus relate eleven indicators of individual openness to innovation, broadly defined (e.g., attitudes toward science and technology, new versus old ideas, change, risk taking, personal agency, imagination and independence in children) to five different measures of religiosity, including beliefs and attendance. We control for all standard socio-demographics as well as country, year and denomination fixed effects. Across the fifty-two estimated specifications, greater religiosity is almost uniformly and very significantly associated to less favorable views of innovation.
Keywords: D83; O31; O35; O43; Z1; Z12; 330; innovation; creativity; science; technical progress; ideas; risk-taking; growth; religion; beliefs; attitudes; values; tolerance; dogma; culture